2006
DOI: 10.1063/1.2357740
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation of NO on Au(111) via electron-hole pair generation

Abstract: Recent experiments have demonstrated the breakdown of the Born-Oppenheimer approximation when NO undergoes inelastic scattering from a Au(111) surface. In this paper, we provide a simple theoretical model for understanding this phenomenon. Our model predicts multiquanta vibrational relaxation through the creation of high-energy electron-hole pair excitations in the metal. Using experimentally determined parameters, our model gives qualitatively accurate predictions for the final vibrational state populations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…As the temperature of the surface becomes larger, the Arrhenius behavior breaks down, and the linear temperature dependence takes over, according to approximation (13b). The pre-exponent of this Arrhenius form, as essentially given by the numerator of (12), is almost independent of the temperature of the surface, and its dependence on the interaction time is shown in Fig. 5.…”
Section: Kinetics and Absolute Excitation Probabilitiesmentioning
confidence: 93%
See 3 more Smart Citations
“…As the temperature of the surface becomes larger, the Arrhenius behavior breaks down, and the linear temperature dependence takes over, according to approximation (13b). The pre-exponent of this Arrhenius form, as essentially given by the numerator of (12), is almost independent of the temperature of the surface, and its dependence on the interaction time is shown in Fig. 5.…”
Section: Kinetics and Absolute Excitation Probabilitiesmentioning
confidence: 93%
“…This leads to eqn (12), which gives the absolute vibrational excitation probability P vv 0 as a function of the interaction time t and surface temperature T S :…”
Section: Kinetics and Absolute Excitation Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…also expected in the interaction of surfaces with initially vibrationally excited molecules. Thus, Shenvi et al 12,13 have been able to explain the observed multi-quantum vibrational relaxation of NO scattered from Au(111) using a model that incorporates electron hopping between the surface and the molecule. More recently, low dimensional calculations performed by Monturet et al 14 suggest that an electronic friction model may also account for many of the results obtained in this kind of experiment.…”
Section: Introductionmentioning
confidence: 99%